Can exercise make our children smarter? - Nenad Stojiljković; Petar Mitić; Goran Sporiš (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2020)
Purpose. The aim of this study is to reveal the effects of exercise on the brain structure and function in children, and to analyze methodological approach applied in the researches of this topic. Methods. This literature review provides an overview of important findings in this fast growing research domain. Results from cross-sectional, longitudinal, and interventional studies of the influence of exercise on the brain structure and function of healthy children are reviewed and discussed. Results. The majority of researches are done as cross sectional studies based on the exploring correlation between the level of physical activity and characteristics of brain structure and function. Results of the studies indicate that exercise has positive correlation with improved cognition and beneficial changes to brain function in children. Physically active children have greater white matter integrity in several white matter tracts (corpus callosum, corona radiata, and superior longitudinal fasciculus), have greater volume of gray matter in the hippocampus and basal ganglia than their physically inactive counterparts. The longitudinal/interventional studies also showed that exercise (mainly aerobic) improve cognitive performance of children and causes changes observed on functional magnetic resonance imaging scans (fMRI) located in prefrontal and parietal regions. Conclusion. Previous researches undoubtable proved that exercise can make positive changes of the brain structures in children, specifically the volume of the hippocampus which is the center of learning and memory. Finally the researchers agree that the most influential type of exercise on changes of brain structure and functions are the aerobic exercises.